HRI as a Phenomenon of Social Interaction - L.E. Motorina (Социальная психология и общество, 2023)
Objective. Development of general theoretical and methodological concepts for the analysis of the interaction "human-robot" as a holistic human-technological gestalt; introduction into scientific circulation of the concept of human-technological reality; the formulation of the author's definition of personal space as a methodological basis for the study of human-technological relations. Background. The creation of high-tech computer cognitive agents and humanoid robots are becoming a priority subject of scientific research in various fields of knowledge. The main difficulty in moving towards any single generally valid results lies in the fact that in each discipline the problem is investigated within the framework of its inherent terminology. The multivariance of interpretations of studies of human-social robot interaction is especially observed between representatives of the humanities, specialists in the field of artificial intelligence and engineering programming. There is a need for a systematic elaboration of the conceptual and categorical apparatus used to describe the phenomena of human-technological reality, in which a person coexists with new technological beings, is called upon to establish a certain level of relations with them, redistribute personal space, and form new models of social interaction. Methodology. Convergent approach, system analysis, principle of integrity, typology of relations "I-Thou" by S.L. Frank. Conclusions. Consideration of the typology of I-Thou relations, the author's definition of personal space, the introduction into scientific circulation of the concept of human-technological reality, highlighting the features of human-technological relations are proposed for use as a conceptual and methodological toolkit for researching human-robot interaction as a phenomenon of social interaction.